PEMBUATAN BAHAN ACUAN BAKU UNTUK ANALISIS SAMPEL BATUBARA: PRODUCTION OF STANDARD REFERENCE MATERIALS FOR COAL SAMPLE ANALYSIS - Firdaus Djabar; Fitro Zamani; Herry Rodiana Eddy (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2023)
A requirement in the ISO 17025-2017 quality control systems is the adaptation of standard reference materials to ensure measurement accuracy and validation. However, standard reference material is expensive with difficult procurement procedures and limited matrices. Therefore, it is necessary for laboratories to produce their own standard reference materials. This study aims to explain the production of internal standard materials of coal from PT Berau Coal concession area at Sambarata mining site, Tasuk Village, Gunung Tabur District, Berau Regency, East Kalimantan Province. The production stages of standard reference materials involve preparation, homogenization, parameter analysis, statistical tests, and sample packaging. The statistical calculations were performed using the F-test/ANOVA single factor/homogeneous sample, Dixon test and Z-Score. Coal samples were also analyzed at seven accredited coal laboratories in Indonesia. The chemical and physical analysis methods used American Standard Testing and Materials (ASTM) and BSI British Standards. The produced in-house standard reference material indicates ash content of 1.36 ± 0.23%, volatile matter of 45.03 ± 1.29%, total sulfur of 0.14 ± 0.07%, calorific value of 7,310 ± 67kal/gr, and specific gravity of 1.30 ± 0.06.